The intelligent systems of automotive active safety - Ivanov, Valentin; Boutylin, Vladimir (Transport, 2002)
The subject of research is the idea of creation automobile systems of active safety basing on predictable use of potential possibilities of a wheel coupling with a road. Together with the generally accepted dependencies between the tire grip µ wheel slip, s, it is expedient to use potential µ-s-curves which can be deduced, having applied some postulates of the friction theory to the process of wheel-road interaction. In the work the basic dependencies for qualitative estimation of the specified components are given. As the result the concept of an intelligent system of active safety which is based on the control philosophy of predictable use of a tire grip is offered.First Published Online: 19 Dec 2011